Pengaruh viral marketing, content marketing, dan media sosial tiktok terhadap minat beli produk jiniso di kota Surabaya - Maghfiratul Layli, Rani; Dermawan, Rizky (Jurnal Riset Pendidikan Ekonomi, 2025)
This study aims to analyze the effect of Viral marketing, content marketing, and social media on buying interest in Jiniso products in Surabaya City. The data analysis technique used is a quantitative analysis approach adopted through the Partial least square (PLS) tool. Inner model analysis is seen from R-Square and predictive relevance (Q2). Researchers used a non-probability sampling method with a purposive sampling technique and collected data through questionnaires from 91 respondents. The results showed that the three variables have a significant influence in increasing consumer buying interest. Viral Marketing is proven effective through product review indicators, where positive customer reviews increase trust and encourage purchases. Content marketing contributes significantly by providing accurate and detailed product descriptions, thus increasing consumer confidence in the information received. Social media plays an important role, especially through the relationships built with followers, which creates emotional closeness and strengthens consumer buying interest. This research shows that a combination of marketing strategies through social media, relevant content, and virality can effectively attract consumers' attention and strengthen Jiniso's brand position in Indonesia's local fashion market.